Soil Incompressibility by 'Mixed' and Penalty Methods. - Borja, Ronaldo I.
In this paper two numerical methods of treating soil incompressibility are discussed, namely : (1) solution by 'mixed' formulation and (2) solution by penalty information. The numerical methods presented herein are finite element based and assume that in the no flow (undrained) condition, the deformation and pore pressure behavior of a saturated soil medium can be analyzed either by considering a two phase soil water relationship or by a single phase continuum formulation.